Legal features of professional and physical training of seafarers - Iryna Pidpala (Kazimierz Wielki University, 2018)
The article is devoted to the study of the specifics of the physical training of the sea crew. The fundamental principle is the connection of physical and sports with labor and defense activities. This connection is manifested in practice through the introduction of special methods of physical training in the organization of work. Vocational and physical training is one of the main directions, which forms knowledge, physical and special qualities, abilities and skills, which contribute to the achievement of the readiness of persons for successful professional activity. Recreational activities that reduce the negative impact on the health of the sea crew are characterized. It is certain that the state of health for suitability for maritime activities depends on medical examinations. Medical examinations are mandatory and have their own frequency, taking into account the position on the ship.